PROSES MANAJEMEN PERKANTORAN DI BADAN PUSAT STATISTIK (BPS) KABUPATEN PIDIE - Armiwal Armiwal (Universitas Jabal Ghafur, 2020)
Every organization that is formed, is cooperation between several people who have a purpose. In the process of achieving that goal many factors are determining, the only regular management factor, the success or failure of an organization or institution is determined from the orderly administration and management and the person who leads the organization concerned. It is clear that a good management arrangement as well as a regular administration will determine the success of a business in every management process to achieve a specific purpose.In order to increase the efficiency and effectiveness of the implementation of office management, it is necessary to implement various office activities based on a system so that the desired goals will reach the target. The tasks assigned to each section must be refused to prevent abuse or overlap in the performance of the task.The skills of an employee is very supportive to the process of office management in an organization, because without a skilled employee it is unlikely to be able to support work activities and can not also improve the ability of work so that the need for guidance on employees continuously. In terms of coaching the employees of the Central Bureau of Statistics (BPS) of Pidie Regency.To overcome this problem, the government has tried to pursue various ways, either by training or upgrading in a staffing field or by creating new, more efficient and effective methods in order to improve the management and administration process by completing the tools that are carried out continuously. However, the fact of office management process in Central Bureau of Statistics (BPS) of Pidie Regency is still in medium category. Keywords: Office Management.